Injection of a polymerized hyaluronic acid/collagen hydrogel matrix in an in vivo porcine disc degeneration model - Omlor, Georg; Lorenz, Helga; Bruckner, Thomas; Richter, Wiltrud; Gühring, Thorsten (European spine journal, 2012)
Disc degeneration and re-herniation after nucleotomy procedures are common problems. Simultaneous application of hyaluronic acid (HA)-based matrix has been proposed to limit disc degeneration. This, however, is hampered by loss of the substituted matrix out of the disc. Hence, in situ polymerization of the injected matrix with ultraviolet light (UVL) directly used after injection may be useful. Therefore, this study evaluates a new HA/collagen hydrogel matrix with in situ polymerization after implantation in an established porcine nucleotomy model.